2018
DOI: 10.1002/jlb.3vmr0118-036r
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-3-binding protein: A multitask glycoprotein with innate immunity functions in viral and bacterial infections

Abstract: Galectin-3-binding protein (Gal-3BP) is a ubiquitous and multifunctional secreted glycoprotein originally identified and mainly studied in the context of neoplastic transformation and cancer progression. However, Gal-3BP expression is induced in viral infection and by a multitude of molecules that either mimic or are characteristic for an ongoing inflammation and microbial infection, such as IFN-α, IFN-β, IFN-γ, TNF-α, poly(I:C), dsRNA, and dsDNA. Furthermore, Gal-3BP belongs to the scavenger receptor cysteine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
75
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(84 citation statements)
references
References 92 publications
(220 reference statements)
1
75
0
Order By: Relevance
“…90 K was initially studied from tumor cells 3 and it is relevant in cancer development and progression 31,32 . It also plays regulatory roles in the immune system; data from the literature concerning the role of 90 K in the immune response has indicated that it may have immunosuppressive as well as immunostimulatory functions depending on the biological context, and it may induce or suppress the secretion of cytokines that play roles in inflammation 1 . It is also induced during viral infections leading to IFN and pro-inflammatory response 33 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…90 K was initially studied from tumor cells 3 and it is relevant in cancer development and progression 31,32 . It also plays regulatory roles in the immune system; data from the literature concerning the role of 90 K in the immune response has indicated that it may have immunosuppressive as well as immunostimulatory functions depending on the biological context, and it may induce or suppress the secretion of cytokines that play roles in inflammation 1 . It is also induced during viral infections leading to IFN and pro-inflammatory response 33 .…”
Section: Discussionmentioning
confidence: 99%
“…90 K has been detected in biological fluids such as blood 1,13,14 , milk 15 , and more recent studies also reported its presence in the CSF 16,17 . In the serum 90 K was found in circulating microparticles, where it was increased for systemic lupus erythematosus and venous thromboembolism patients 18 .…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Unsurprisingly, Ctsk, Ifitm3, CD36, Lgals3bp, which are known to be modulated by inflammatory cytokines, were among those reduced in SKO macrophages. [ 14 ] Ctsk is also expressed in significant levels in human breast cancers and has been shown to play an important role in tumor invasiveness. [ 15 ] Similarly, Lgals3bp belongs to the scavenger receptor and its expression is induced during viral and microbial infection as well as the presence of pathogen‐associated molecular pattern, such as poly(I:C), dsRNA, and dsDNA.…”
Section: Figurementioning
confidence: 99%
“…Notably, Galectin-3-binding protein (Lgals3bp) is a protein whose expression is mediated by the canonical activation of the activation of the NF-κB signaling pathway, upon TNFα stimulus (Noma et al, 2012). Lgals3b has been previously demonstrated to induce increased secretion of IL-6 in several different cell lines (Loimaranta et al, 2018), and also promote monocyte migration (Sano et al, 2000). Our results show that TNFα not only promotes the release of Lgals3bp in adipocytes, but its secretion levels increase with prolonged TNFα treatment.…”
Section: Chronic Tnfα Treatment Promotes Differential Regulation Of Smentioning
confidence: 99%